Meningkatkan Profitabilitas UMKM Pengrajin Gerabah dengan Efisiensi Keuangan dan Optimalisasi Produksi - Maryam, Maryam; Nengsih, Rita; Makmur, Teuku; Susanti, Susanti; Arsyad, Arsyad; Rahmi, Ayu Rahmi (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This article aims to analyze strategies for enhancing the profitability of pottery SMEs through financial efficiency and production optimization. The methods employed include literature review, secondary data analysis, and case studies focusing on operational cost management, product diversification, and digital marketing. The study identifies key gaps, such as inefficient capital management and reliance on traditional production methods, which lead to low profit margins and limited market access. The findings reveal that financial efficiency strategies, such as cash flow management and stock control, can reduce operational costs by up to 20%. Additionally, production optimization through simple technologies, like automated drying ovens, increases daily productivity by 30%. Product diversification and digital marketing effectively expand market reach, stabilize revenues, and enhance competitiveness in local and global markets. The implications of this research emphasize the importance of integrating operational efficiency, product innovation, and risk management to achieve sustainable growth. This article contributes practical guidelines for pottery SMEs to improve profitability and ensure business sustainability in dynamic economic environments.